Disain dan Uji Kinerja Pengering Rotari Tumpukan untuk Pengeringan Jagung Pipilan - Sulikah .; Leopold Oscar Nelwan; I Nengah Suastawa (PERTETA, 2008)
A rotary bed dryer for grain had been developed and tested in this study. The dryer was designed in order to provide an effective mixing effect. The dryer used perforated cylindrical drum for its chamber and was rotated by an electrical motor. The result showed that when the numbers of rotation was 20, the shelled corn had been mixed effectively. To meet this condition, the drum was rotated for 5 minutes every 15 minutes during the drying process. As the result, the variation of moisture Qontent in radial direction was less than 1.1% w.b. With drying air temperature of 670C and 600C the specific energy consumption of the dryer were 5.6 MJ/kg to reduce the moisture content from 25 to 16% b.b. and 5.4 MJ/kg from 17 to 13% w.b. Thermal energy was the highest contributor of total energy consumption. As it had been expected, the full load of the dryer provided a lower mechanical energy requirement than the half load. Keywords: rotary bed dryer, mixing, specific energy consumption Diterima: 5 Februari 2008; Disetujui: 10 Juni 2008